Fleishman is in trouble : a novel - Brodesser-Akner, Taffy (Random House, 2020)
Divorcing his hostile wife when he concludes he could find genuine happiness elsewhere, Dr. Toby Fleishman is astonished when his ex abruptly disappears, leaving him unable to move on without acknowledging painful truths about his marriage.